Turkey - Topbaş, Seyhun; Bulut, Talat; Günhan, Nazmiye Evra (Taylor and Francis, 2019)
This book is about the management of children and young people with developmental language disorders (DLD). DLD is a relatively common condition affecting children and young people. The latest figures suggest that 9 per cent of children experience it at school entry. DLD occurs when the child’s language skills are judged to be significantly delayed relative to those of children of the same age. This judgement is usually made by means of a combination of formal assessment, observations of linguistic performance and professional judgement.
Keywords: Behavioral Sciences; Education; Health and Social Care; Language & Literature